FRACTIONAL EQUIAFFINE CURVATURES OF CURVES IN 3-DIMENSIONAL AFFINE SPACE - Aydin, Muhittin Evren; Kaya, Seyma (Bayram Sahin, 2023)
In this study, we investigate the equiaffine invariants of a parametrized curve in the 3-dimensional affine space R3 by using a simplification of Caputo fractional deriva-tive. We introduce the so-called fractional equiaffine arclength function for a non-degenerate parametrized curve, providing the notions of fractional equiaffine frame and curvatures. Fur-thermore, we give the relations between the fractional and standard equiaffine curvatures. © 2023, Bayram Sahin. All rights reserved.
Keywords: Affine differential geometry; Caputo fractional derivative; Equiaffine arclength; Equiaffine curvature